Validity and Reliability of the Nepali Version of the General Oral Health Assessment Index (Gohai) in Nepali Population - Singh, Tanuja; Ghimire, Tika Ram (Birat Journal of Health Sciences, 2020)
Introduction: Oral health problems are more chronic and severe. Various instruments have been developed to measure Oral Health Quality of Life. General Oral Health Assessment Index (GOHAI) is a well-established, frequently used questionnaire for measuring OHQoL for geriatric and general population. Objectives: The objective of the study is to translate the GOHAI in Nepali and to assess its reliability and validity. Methodology: This study was conducted on the patient attending department of Prosthodontics, Kathmandu University School of Medical Sciences from March 2017 to February 2018. The GOHAI questionnaire was translated into Nepali version from English and back translated. Nepali version of GOHAI was pilot tested on 50 adult population to test the comprehensibility of the questionnaire, and then required alterations were done. The final Nepali version of GOHAI was administered to 301 (aged 20-70 years) adults along with the self-informed questionnaire. Clinical examination was done on the same day by a single examiner using World Health Organization (WHO) criteria. Reliability was analyzed using test-retest, cronbach alpha and split half reliability. For validity, discriminant validity and construct validity were calculated. Results: Cronbach's alpha was 0.749, which indicated good overall internal consistency and homogeneity. For test-retest, the spearman's rho correlation coefficient between visits ranged from 0.641-0.952 for all twelve questionnaires indicating strong correlation with p-value< 0.001. Conclusion Nepali version of the GOHAI exhibited acceptable reliability and validity in the people of Kathmandu valley, Nepal. This instrument can be applied to evaluate OHRQoL of different age groups as it was carried out in all the age groups.